Implementasi Program Tahfidz Al-Qur'an dengan Metode Bil Qolam di MTs Hasyim Asy'ari Kota Batu - Ety, Elmazaya; Ahmad Ma’ruf (al-Iltizam: Jurnal Pendidikan Agama Islam, 2025)
This research aims to document the implementation of the Tahfidz Al-Qur'an program at MTs Hasyim Asy'ari Batu City using the Bil Qolam technique and identify the factors that influence its success. The approach applied is qualitative with a case study method. Research techniques include document analysis in the form of student tahfidz reading data, observation, and in-depth interviews with students, mentors, and tahfidz coordinators. The findings reveal that the program's implementation involves stages like Deepening Understanding of the Qur'an (PPQ), Bin Nadzor, and tahfidz. Supporting factors include the method's simplicity, competent teachers with clear sanad, student motivation, and dynamic class models. Challenges include maintaining student consistency, managing academic burdens, ensuring reading and memorization accuracy, and preserving memorization quality.